Feedback from lateral occipital cortex to V1/V2 triggers object completion: Evidence from functional magnetic resonance imaging and dynamic causal modeling. Issue 17 (21st August 2021) - Chen, Siyi; Weidner, Ralph; Zeng, Hang; Fink, Gereon R.; Müller, Hermann J.; Conci, Markus
Abstract: Illusory figures demonstrate the visual system's ability to integrate disparate parts into coherent wholes. We probed this object integration process by either presenting an integrated diamond shape or a comparable ungrouped configuration that did not render a complete object. Two tasks were used that either required localization of a target dot (relative to the presented configuration) or discrimination of the dot's luminance. The results showed that only when the configuration was task relevant (in the localization task), performance benefited from the presentation of an integrated object. Concurrent functional magnetic resonance imaging was performed and analyzed using dynamic causal modeling to investigate the (causal) relationship between regions that are associated with illusory figure completion. We found object‐specific feedback connections between the lateral occipital cortex (LOC) and early visual cortex (V1/V2). These modulatory connections persisted across task demands and hemispheres. Our results thus provide direct evidence that interactions between mid‐level and early visual processing regions engage in illusory figure perception. These data suggest that LOC first integrates inputs from multiple neurons in lower‐level cortices, generating a global shape representation while more fine‐graded object details are then determined via feedback to early visual areas, independently of the current task demands. Abstract : The visual system has a remarkable ability to integrate disparate parts into coherent whole objects, as illustrated, for example, by the perception of illusory figures. This study investigates connectivity patterns associated with illusory figures and provides direct evidence that the formation of completed objects relies on feedback connections from mid‐level to early visual processing regions: LOC first generates a global shape representation while more fine‐graded object details are then determined via (back‐) projections to early visual areas, independently of the current task demands.